Securities Analysts and Incumbent Response to Radical Technological Change: Evidence from Digital Photography and Internet Telephony - Benner, Mary J. (Organization Science, 2010)
A large body of research has explored the factors that impede established firms' responses to radical technological changes. While it is widely acknowledged that managers face pressures from financial markets to choose strategies that maximize shareholder value, little work in the technological change literature has considered the possible influences of public equity markets and the securities analysts who mediate them on incumbent firms challenged with technological change. In this paper, I begin to address the topic by empirically exploring how securities analysts react to the different strategies undertaken by incumbent firms faced with radical technological change. I study the question in two settings: the shift to digital technology in photography and the advent of Voice over Internet Protocol (VoIP) technology in wireline telecommunications. I find evidence that analysts are more attentive and positive toward incumbents' strategies that extend and preserve the existing technology than toward strategies that respond directly to the new technology. In these settings, analysts largely ignore incumbents' strategies that directly incorporate the new technology for several years following the discontinuity. This study provides insights into the nature and direction of analysts' reactions to firms' strategies in the context of technological change, and is a first step toward better understanding of the potential role of analysts' and financial markets in incumbent adaptation.